Penguatan Kompetensi Pelaku UMKM dalam Penerapan Strategi Digital Marketing melalui Kegiatan Seminar - Angelia Putriana; Romindo Romindo (Yayasan Literasi Sains Indonesia, 2025)
Usaha Mikro, Kecil, dan Menengah (UMKM) play a strategic role in promoting economic growth and job creation. However, many UMKM actors still face limitations in optimally utilizing digital marketing strategies due to low digital literacy and limited understanding of technology-based marketing. This community service activity aims to strengthen the competencies of UMKM actors in implementing digital marketing strategies through an educational and practical seminar. The activity was conducted on Saturday, March 22, 2025, from 15:00 to 18:00 WIB, located at Jl. Pertahanan No. 32, Timbang Deli, Medan Amplas District, Medan City, North Sumatra (GBI Metro Building). The implementation methods included material presentations, interactive discussions, and question-and-answer sessions covering fundamental concepts of digital marketing, the use of social media as a promotional tool, digital content creation strategies, and the introduction of relevant digital marketing platforms for UMKM. The results of the activity indicate an increase in UMKM actors’ understanding, awareness, and motivation regarding the importance of digital marketing in enhancing business competitiveness. This seminar contributes to improving the digital literacy of UMKM actors and encourages the adoption of more adaptive and sustainable marketing strategies in the era of digital transformation.